Exploration of urease-aided calcium carbonate mineralization by enzyme analyses of Neobacillus mesonae strain NS-6 - Zhiwei Ma; Mengyao Chen; Juncheng Lu; Shichuang Liu; Yanling Ma (Microbiology Spectrum)
ABSTRACT Urease containing nickel cofactor is crucial for urea-hydrolytic induced calcium carbonate (CaCO3) precipitation (UICP). However, limited information exists regarding the influence of amino acid residues interacting with nickel ions in its structure on induced CaCO3 mineralization. Herein, RT-qPCR was used to demonstrate that the addition of NiCl2 dramatically upregulated the expression of urease structural gene ureC that was correlated with nickel binding in Neobacillus mesonae strain NS-6. Homology modeling and molecular docking were employed to construct the three-dimensional structure of urease and seek the key residues involved in nickel binding process, and virtual mutation technology was adopted to inform three key residues coordinated with nickel ions and urea, His249, His275, and Asp363. Four metrics, including root mean square deviation values for mutations of those key residues in urease-urea complexes severally and wild-type, were calculated by molecular dynamics simulations when they were mutated into alanine, respectively. Subsequently, the mutations of H249A, H275A, and D363A were characterized using western blotting to reveal a decrease in the relative expression and activity of urease, along with a corresponding reduction in CaCO3 precipitation. Ultimately, the mutations also exhibited that they had lower substrate affinity and catalytic efficiency for urea through enzymatic properties analysis. The findings suggested that those residues played a pivotal role in UICP of strain NS-6, which would expand the theoretical basis for modulating urease activity.IMPORTANCEUrease-producing bacterium is of great importance in diverse application fields, such as environmental remediation, due to its key driving characteristics in catalyzing urea hydrolysis via urea-hydrolytic induced CaCO3 precipitation (UICP). As essential cofactors of urease, nickel ions play a crucial role in regulating urease catalysis and maintaining structural stability. Numerous investigations have emphasized the impact of nickel ions on urease activity in recent years, to our best knowledge, only a few literatures have studied the molecular-level regulation of nickel-ligand residues. This study focused on the highly urease-producing bacterial Neobacillus mesonae NS-6 to explore the effects of specific nickel-ligand residues on the urease-aided CaCO3 mineralization process using molecular simulation predictions and targeted mutation experiments. The aim was to provide a molecular-level understanding of the interactive effects between urea and critical residues associated with the urease active center, as well as propose an effective modification strategy to enhance the application of UICP in future environmental areas.